ONLINE MEDIA DISCOURSE ANALYSIS RELATED TO THE IMPLEMENTATION OF THE RECAPITULATION INFORMATION SYSTEM (SIREKAP) FOR THE 2024 GENERAL ELECTION - Subekti, Dimas (Jurnal Politik Pemerintahan Dharma Praja, 2024)
The purpose of this study is to explain the discourse in online media related to the implementation of Sirekap in the 2024 elections. This research uses a qualitative method with a case study approach. The findings in this study explain that there are four crucial issues in the news in online media related to the problem of using Sirekap by the KPU in the 2024 elections, namely photo converstion errors of vote counting result documents, KPPS officers have difficulty accessing, application security and alleged election fraud. From the perspective of online media coverage, Tempo.co Kompas.com and Detiknews.com were found to be massively reporting on KPPS officers having difficulty accessing. Meanwhile, CNNIndonesia online media has two dominant issues in its news, namely the problem of KPSS having difficulty accessing the Sirekap application and alleged election fraud. Furthermore, conversations in online media are still very dominant in discussing election results in the context of the vote data entered in Sirekap and the performance of the KPU and KPPS. Then, the network of actors discussed in the online media is the KPU and Bawaslu as election organizers. Then, Anies Baswedan and the head of campaign team 01 as a candidate pair competing in the 2024 election. Furthermore, Ganjar Pranowo and Mahfud MD as candidate pair number 3 who also competed in the 2024 elections. Likewise, actors outside election participants, namely political observers, information technology experts and netizens.